2011
DOI: 10.1086/660363
|View full text |Cite
|
Sign up to set email alerts
|

The Role Played by Contaminated Surfaces in the Transmission of Nosocomial Pathogens

Abstract: Studies in the 1970s and 1980s suggested that environmental surface contamination played a negligible role in the endemic transmission of healthcare-associated infections. However, recent studies have demonstrated that several major nosocomial pathogens are shed by patients and contaminate hospital surfaces at concentrations sufficient for transmission, survive for extended periods, persist despite attempts to disinfect or remove them, and can be transferred to the hands of healthcare workers. Evidence is accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
434
1
21

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 559 publications
(460 citation statements)
references
References 107 publications
4
434
1
21
Order By: Relevance
“…Complementary studies have shown that the application of air cleaning technologies can reduce surface contamination [6]; while others have highlighted that environmental contamination, through the deposition on surfaces, cannot be underestimated in the contribution to fomite-based transmission [7,8,9]. That said, the fate of aerial pathogens in indoor environments is still poorly understood and constitutes an area of much controversy and challenging research.…”
Section: Introductionmentioning
confidence: 99%
“…Complementary studies have shown that the application of air cleaning technologies can reduce surface contamination [6]; while others have highlighted that environmental contamination, through the deposition on surfaces, cannot be underestimated in the contribution to fomite-based transmission [7,8,9]. That said, the fate of aerial pathogens in indoor environments is still poorly understood and constitutes an area of much controversy and challenging research.…”
Section: Introductionmentioning
confidence: 99%
“…9 Along with Staphylococcus and Streptococcus, Enterobacteriaceae is family of bacteria which commonly causes diseases to humans, like bacteremia, pneumonia, and hospitalacquired urinary tract infection. 9,12 If it appears on the other places which it is supposed to live, such as in urinary tract, abdomen, blood vessels, prostate gland, pulmonary, bone and meninges, it will cause diseases. 9 The appearance of ESBL-producing Enterobacteriaceae also has widely known in the world of health, but result of resistance test that had done to Enterobacteriaceae in this study was satisfying.…”
Section: Resultsmentioning
confidence: 99%
“…12 The presence of Pseudomonas aeruginosa in humid surfaces inhospital means those surfaces needed to be cleaned thoroughly. 9,13 The features of Pseudomonas aeruginosa are widely found in soil and water, also it is usually found in intestine and human skins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of Acinetobacter baumannii identified in NFGNB in our study is higher than the 28.57% reported by Liazid (2016) for Tlemcen hospital in Algeria. Acinetobacter baumannii can persist for three days to five months and can survive on dry surfaces (Kramer et al, 2006, Otter et al, 2011. It can cause high mortality, up to 35% (Antunes et al, 2014).…”
Section: Distribution Of Distribution Of Nfgnbmentioning
confidence: 99%